Dupont d’Avignon (1971-2017), simultanément au cœur et à la marge de la géographie française - Christian Grataloup (Bulletin de l’Association de Géographes Français)
For 46 years a group of geographers met to work collectively on the transformation of geography in France, and a little beyond. There are few other examples, in human sciences, of such a collective intellectual sustainable. On October 14th, 2017, the AGF gave it the floor.